2022
DOI: 10.1057/s41264-022-00158-9
|View full text |Cite
|
Sign up to set email alerts
|

Designing for loyalty programme effectiveness in the financial services industry

Abstract: This study extends and tests a model determining how customer perceived benefits affect perceived relationship investment and brand relationship quality as mediators to behavioural and attitudinal loyalty with type and timing of rewards as moderators. A quantitative methodology and survey approach was applied using randomly selected stratified sampling resulting in 277 financial services loyalty programme member respondents. The hypotheses were tested using structural equation modelling. The results highlight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 82 publications
(136 reference statements)
0
2
0
Order By: Relevance
“…The reported studies by Brink were conducted before the effective date of IFRS 15. Other CCRPrelated studies (Amalyan and Amalian, 2015;Bernoully and Wondabio, 2019;Brink, 2013Brink, , 2014Brink, , 2016Chapple et al, 2010;Chun et al, 2020;Fourie, 2018;Johansson and Ringius, 2007;Levanti, 2020;Pidduck et al, 2019;Sava, 2014), however also did not include any reference to accounting theory. After the effective date of IFRS 15 no research specifically related to accounting for CCRP transactions could be found.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reported studies by Brink were conducted before the effective date of IFRS 15. Other CCRPrelated studies (Amalyan and Amalian, 2015;Bernoully and Wondabio, 2019;Brink, 2013Brink, , 2014Brink, , 2016Chapple et al, 2010;Chun et al, 2020;Fourie, 2018;Johansson and Ringius, 2007;Levanti, 2020;Pidduck et al, 2019;Sava, 2014), however also did not include any reference to accounting theory. After the effective date of IFRS 15 no research specifically related to accounting for CCRP transactions could be found.…”
Section: Introductionmentioning
confidence: 99%
“…, 2010; Chun et al. , 2020; Fourie, 2018; Johansson and Ringius, 2007; Levanti, 2020; Pidduck et al. , 2019; Sava, 2014), however also did not include any reference to accounting theory.…”
Section: Introductionmentioning
confidence: 99%